Imaging wisely: patient safety in CT. - Lu, Zheng; Thomas, Stephen (Abdominal Radiology, 2016)
The past decade has seen a significant growth in diagnostic CT imaging as a direct result of the clinical value provided by CT imaging. At the same time, many new techniques and resources are now available to make CT imaging safe. This article presents the basics of CT dosimetry and their usage in clinical practices, methods to implement CT dose reduction, followed by a summary of legislation, and guidelines related to patient safety in diagnostic CT imaging. Also, CT radiation dose diagnostic reference levels from published regional and national surveys are reviewed and applied in a CT dose tracking and monitoring program.